2020
DOI: 10.1136/bmjqs-2020-011312
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of reported suicide deaths and attempts on veterans health administration campuses and inpatient units

Abstract: IntroductionSuicide is the 10th leading cause of death in the USA. Inpatient suicide is the fourth most common sentinel event reported to the Joint Commission. This study reviewed root cause analysis (RCA) reports of suicide events by hospital unit to provide suicide prevention recommendations for each area.MethodsThis is a retrospective analysis of reported suicide deaths and attempts in the US Veterans Health Administration (VHA) hospitals. We searched the VHA National Center for Patient Safety RCA database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It can be seen from the above tests that the multi-channel real-time in vivo monitoring system for drug metabolism of small animals based on fluorescence proposed in this paper can achieve long-term continuous in vivo monitoring to meet the needs of in vivo monitoring of small animals. This method can replace some existing methods for acquiring blood concentration data, such as traditional methods for obtaining blood samples, high-performance liquid chromatography [26,27] and retrospective analysis methods [28,29]. three mice were killed at each time point to draw blood and collect organs for calculation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen from the above tests that the multi-channel real-time in vivo monitoring system for drug metabolism of small animals based on fluorescence proposed in this paper can achieve long-term continuous in vivo monitoring to meet the needs of in vivo monitoring of small animals. This method can replace some existing methods for acquiring blood concentration data, such as traditional methods for obtaining blood samples, high-performance liquid chromatography [26,27] and retrospective analysis methods [28,29]. three mice were killed at each time point to draw blood and collect organs for calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation of VHA hemodialysis-related bleeding events reinforced the well-recognized notion that multiple root causes underlie a patient harm event. 11 The action plans, however, ranged from weak to strong recommendations as identified by the VHA NCPS Action Hierarchy for Root Cause Analysis. 26 Updating existing policy and procedures or creating new or revised training is considered a weaker mitigation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Veterans Health Administration policy and prior NCPS publications have documented the process for reporting and investigating VHA patient safety events designed to be nonpunitive, identify root causes, and correct systems issues through action plans to mitigate future risk. 10,11 From January 2000 to June 2018, NCPS collected patient safety reports and RCA data in the SPOT database. In June 2018, collection of VHA patient safety reports was transitioned to the NCPS Joint Patient Safety Reporting (JPSR) system as a collaboration with the Department of Defense.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As recommended by the authors of a recent paper based on VHA postsuicide incident reports, different hospital and community settings need specific suicide prevention measures. 8 System-wide changes in mental health services can also improve safety. In a national before-and-after study conducted using NCISH data, we found that changes to mental health service provision designed to improve safety were indeed associated with lower suicide rates.…”
mentioning
confidence: 99%